Perception of End Users on I-Kelahiran in Sabah, Malaysia - Dhesi Baha, Raja Selva Raja; Cheah, W.L (Australasian College of Health Informatics, 2014)
I-Kelahiran (Inovasi-Kelahiran) is a health informatics system that manages birth data developed and implemented in Sabah to intervene birthing discrepancy, delayed reporting of high risk pregnancy and immunization coverage. Since its implementation, there has not been any formal evaluation on the acceptance of the system. This study aims to assess the perception and acceptance of i-Kelahiran among the nurses in Sabah Health Department. It was a cross-sectional web-based study, conducted on February 2013 among nurses actively working with i-Kelahiran in 21 hospitals and 292 health clinics. A 12-items questionnaire based on “perceived usefulness" and “perceived ease-of-use", adapted from technology acceptance model (TAM) was used for data collection. Data was analyzed using SPSS version 21. A total of 800 nurses participated in this study, with a mean age of 33.62 years (SD=8.060) and majority of them are community and staff nurses. About 63% of them are from primary health clinics and only 6.3% do not have any experience with computer. Mean score for both perceived usefulness 6.11 (SD=1.058) and perceived ease of use 6.14 (SD=0.952) were found to be high. Significant associations were found between perceived usefulness (p=0.001) and perceived ease of use (p=0.008) towards place of work. Significant higher score in perceived ease of use (p=0.033) and perceived usefulness (p=0.047) were found among nurses who have qualification at degree level or higher than those who have diploma. Though the study indicates that overall perceived usefulness and perceived ease of use were high, future study is needed to assess the effectiveness of this system as a whole using other study models.